2021
DOI: 10.3390/molecules26092811
|View full text |Cite
|
Sign up to set email alerts
|

The Different Facets of Triclocarban: A Review

Abstract: In the late 1930s and early 1940s, it was discovered that the substitution on aromatic rings of hydrogen atoms with chlorine yielded a novel chemistry of antimicrobials. However, within a few years, many of these compounds and formulations showed adverse effects, including human toxicity, ecotoxicity, and unwanted environmental persistence and bioaccumulation, quickly leading to regulatory bans and phase-outs. Among these, the triclocarban, a polychlorinated aromatic antimicrobial agent, was employed as a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 108 publications
0
26
0
Order By: Relevance
“…Sorafenib and several of the compounds identified in our screen are diarylureas, which has served as an important molecular scaffold in anticancer drug development [50,51]. A growing body of work shows a strong potential for the use of the diarylurea scaffold in the development of antiviral, antiparasite, antibacterial and antifungal compounds [52][53][54]. Sorafenib in particular is reported to possess activity against drug-resistant Staphylococcus aureus and to interfere with replication of New World alphaviruses through a mechanism that is independent of host cell kinase inhibition [55].…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib and several of the compounds identified in our screen are diarylureas, which has served as an important molecular scaffold in anticancer drug development [50,51]. A growing body of work shows a strong potential for the use of the diarylurea scaffold in the development of antiviral, antiparasite, antibacterial and antifungal compounds [52][53][54]. Sorafenib in particular is reported to possess activity against drug-resistant Staphylococcus aureus and to interfere with replication of New World alphaviruses through a mechanism that is independent of host cell kinase inhibition [55].…”
Section: Discussionmentioning
confidence: 99%
“…One epidemiologic study also indicated that PrPB is considerably associated with DNA damage in human sperm [12]. Furthermore, two antibacterial ingredients, TCS and triclocarban (TCCB), are frequently used in >2000 products, including PCPs (e.g., toothpaste and hand soap); detergents and plastics are also EDCs, and are found in a wide variety of matrixes worldwide [13,14]. Dermal absorption from PCPs is the primary route for human exposure to TCCB or TCS because of their high concentrations (0.1-0.3% [w/w]) [13][14][15]; both have been detected in human blood and urine [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Triclocarban (TCC, Figure 1), N-(4-chlorophenyl)-N'- (3,4-dichlorophenyl) urea, is a polychlorinated aromatic antimicrobial that has been used in personal care products for over 60 years [1] for the prevention of spoilage and infections as it perturbs microbial fatty acid synthesis and cell membrane formation of microbes [2,3]. It belongs to the class of diarylureas (or bis-phenylureas), commonly known for their antitumor properties [4] and numerous other biological activities, and it has been recently proposed for a repositioning to antimicrobial [5] and/or for the treatment of COVID-19 [6].…”
Section: Introductionmentioning
confidence: 99%
“…TCC is added, as a preservative, into consumer products including toothpastes, baby teethers, cosmetics, household sponges, plastic cutting boards, socks and undergarments [7,8]. It is metabolized to hydroxylated species and glucuronides [2,9] and detected in human tissue such as fingernails and body fluids, including blood, urine and seminal plasma [10][11][12]. Nevertheless, given its broad use in personal care products, some concerns about its endocrine disruptive properties were raised [13].…”
Section: Introductionmentioning
confidence: 99%